2020
DOI: 10.1001/jamaoncol.2020.3697
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Discuss Clinical Trials Among Black vs White Men With Prostate Cancer

Abstract: IMPORTANCE Black individuals are underrepresented in cancer clinical trials. OBJECTIVE To examine whether Black and White men with prostate cancer differ in their willingness to discuss clinical trials with their physicians and, if so, whether patient-level barriers statistically mediate racial differences. DESIGN, SETTING, AND PARTICIPANTSThis cross-sectional survey study used baseline data from Partnering Around Cancer Clinical Trials, a randomized clinical trial to increase Black individuals' enrollment in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…The fact that historically disadvantaged patients are less trusting of clinical research is well founded, given the tragic history of medical experimentation in the United States, exemplified by the infamous Tuskegee syphilis study. 97,98 However, most patients will readily participate in a trial, as evidenced in a recent systematic review and meta-analysis, which showed that more than half of patients offered a trial by their physician agreed to participate. Critically, the study also showed that non-Hispanic Black, Hispanic, and Asian patients were willing to participate at rates on par with or even higher than non-Hispanic White patients.…”
Section: Patient-level Factorsmentioning
confidence: 99%
“…The fact that historically disadvantaged patients are less trusting of clinical research is well founded, given the tragic history of medical experimentation in the United States, exemplified by the infamous Tuskegee syphilis study. 97,98 However, most patients will readily participate in a trial, as evidenced in a recent systematic review and meta-analysis, which showed that more than half of patients offered a trial by their physician agreed to participate. Critically, the study also showed that non-Hispanic Black, Hispanic, and Asian patients were willing to participate at rates on par with or even higher than non-Hispanic White patients.…”
Section: Patient-level Factorsmentioning
confidence: 99%
“…Additionally, clinician communication quality and quantity, including specific framing of phase 1 trials, might affect patient willingness to participate 15,16 . Prior work has also suggested that Black patients with prostate cancer are less willing to discuss cancer clinical trials 18 . Risk perceptions may also play a role, with prior work suggesting that non‐White and/or Hispanic patients may be more likely than White and/or non‐Hispanic patients to perceive phase 1 trials to have a high level of risk 8 …”
Section: Discussionmentioning
confidence: 99%
“…High levels of patient mistrust was also associated with less favorable physician perceptions of Black patients, which, in turn, affected physician perceptions of how well these patients would tolerate treatments ( 68 ). A more recent study found that Black men with prostate cancer had higher levels of group-based medical suspicion than White men, and this race-based attitude was associated with less willingness to discuss clinical trials with their physicians ( 69 ). More current research is examining how patient and oncologist nonverbal communication may be associated with these race-based attitudes ( 70 , 71 ).…”
Section: Patient-physician Communication and Disparities: First Second And Third Generation Studiesmentioning
confidence: 99%